Pengembangan Media Lift The Flap Book Berbasis Model Direct Instruction Untuk Meningkatkan Keterampilan Menulis Kalimat Langsung dan Tidak Langsung Siswa - Karimah, Atha Nur; Atha Nur; Sismulyasih Sb, Nugraheti (Paedagogie, 2026)
This study was motivated by the poor writing skills of fifth-grade elementary school students, especially in direct and indirect sentences. The purpose of this study was to develop a "Foldable Book" learning tool based on the Direct Instruction paradigm and assess its feasibility and effectiveness in improving students' direct and indirect writing skills. The research and development (R&D) approach for this study followed Borg and Gall's eight-stage development model. These stages are as follows: (1) information gathering and research; (2) planning; (3) product development in its initial form; (4) limited trial; (5) product revision; (6) field or large-scale trial; (7) final product revision; and (8) dissemination and implementation. Data were collected using tests (pre-test and post-test) and non-test methods (observation, interviews, questionnaires, and documentation). The subjects of the study were fifth grade V B students from SDN Tambangan 02. The initial data were analyzed using a normality test, while the final data were analyzed using a paired sample t-test and an N-Gain test. Based on the results of the feasibility test, which showed an evaluation percentage of 93.3% from media expert validators and 91.67% from subject matter experts, the media was categorized as "very feasible". The results of the efficacy test showed an N-Gain score of 0.4214 (moderate category) for small-scale trials and 0.47547 (moderate category) for large-group trials. The t-test results showed a significance value of 0.000 (<0.05) with an average pre-test score of 50.5 and an average post-test score of 74.5. There was an average difference of 24 points between the pre-test and post-test results. As a result, the "Lift-Close Book" media, which is based on the Direct Teaching paradigm, is useful and effective in helping fifth grade students of SDN Tambangan 02 in making direct and indirect sentences.